Miratu'lEbdan Fi Tesrih-i Azaul-Insan: First printed illustrated anatomy book in Ottoman-Turkish medicine - Ortuğ, Gürsel; Ortuğ, Alpen; Kurt, N. K. (Via Medica, 2018)
Background: Medical education in Ottoman-Turkish medicine was shaped by the influence of Claudius Galenus (c.130-c.210) and Ibn-i Sina (c.980-c.1037). These teachings were performed in madrasahs until the beginning of the 19th century. Within the scope of master-apprentice relationship, medical training was also given in private clinics. As a result of religious and social pressures on scientific studies, human cadavers were never used because they were considered sacred. For centuries, all books were handwritten in the Ottoman Empire until the first printing press was established in Istanbul during 1726. However, the first illustrated book on anatomy was not printed until another 100 years later. Materials and methods: A comparative study was conducted on the anatomical drawings in "Miratu'l Ebdan Fi Tesrih-i Azau'l Insan" (Ataullah SM, 17th), and significance of this book. Results: Forty-six out of 56 figures were received from the book of physician and anatomist Jean Palfin (1650-1730). Remaining 9 figures were cited from author himself as collected from Bernard Siegfried Albinus (1697-1170), Raymond Vieussens (1614-1715), R. Drake (1667-1707), Clopton Havers (1657-1702), Albrecht von Haller (1708-1777), Joseph Guichard Duverney (1648-1730). The figures were drawn exactly the same way with minimal changes. Main text of the book is mostly translation from Italian edition of Bertin and Palfin's Works. The book is not only the first printed anatomical book but also the first printed work in Ottoman-Turkish medicine. Another very significant aspect of the illustrations are perspective drawing figures which differ from miniature style drawings of the past. Conclusions: Sanizade Ataullah's work has a significant value not only for being the first printed illustrated anatomy book which makes it more approachable but also for providing anatomical drawings as illustrations not as miniature style painting.
WOS: 000452416600023
PubMed ID: 29651793
Keywords: Sanizade Ataullah Mehmed Efendi; Chani-Zadeh; Ottoman-Turkish Medicine; History of Anatomy